2012
DOI: 10.1055/s-0032-1304606
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Changes of Carotid Wall Properties in Patients with Acromegaly are not Restored after 1 year of GH/IGF1 Normalization

Abstract: Both the controlled and active ACM patients showed structural arterial changes. After 1 year of disease control, the patients with controlled ACM showed improvements in the functional, but not the structural, arterial parameters compared with the patients with an active condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Data previously published by our group [19] showed that both controlled and active ACM patients have structural (higher intima-media thickness) and functional (higher augmentation index and pulse wave velocity) arterial changes. Large artery stiffening might have important implications for cardiac morphology and performance as well as increasing the susceptibility to atheromatous disease and hence subendocardial ischemia, contributing therefore to LV longitudinal dysfunction [31].…”
Section: Acromegalic Cardiomyopathy and Ventricular Mechanicsmentioning
confidence: 60%
See 2 more Smart Citations
“…Data previously published by our group [19] showed that both controlled and active ACM patients have structural (higher intima-media thickness) and functional (higher augmentation index and pulse wave velocity) arterial changes. Large artery stiffening might have important implications for cardiac morphology and performance as well as increasing the susceptibility to atheromatous disease and hence subendocardial ischemia, contributing therefore to LV longitudinal dysfunction [31].…”
Section: Acromegalic Cardiomyopathy and Ventricular Mechanicsmentioning
confidence: 60%
“…All subjects were evaluated according to a standardized protocol as reported before [19] deriving the main indices of arterial stiffness [the b index, arterial compliance (AC), augmentation index (AIx), local pulse wave velocity (PWV), and pressure-strain elastic modulus (Ep)] from their means over five beats, according to established and validated formulas [20,21].…”
Section: Carotid Ultrasoundmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased cIMT has been measured in adults with acromegaly [8,9] . GH is discussed to be a mediator of inflammatory mechanisms underlying atherogenesis through direct effects [10] .…”
mentioning
confidence: 99%
“…Further proposed mechanisms are dyslipidemia, insulin resistance, hyperglycemia, and increased IGF-1 concentrations [6] . Therefore, it is conceivable that at least the administration of supraphysiological doses of GH, such as in small for gestational age (SGA), stature homeobox containing gene (SHOX) deficiency, or Turner syndrome, could have negative effects on the cardiovascular system [8] . Indeed, first reports from France of the long-term mortality and morbidity after GH treatment in childhood (SAGhE study) reported an increased mortality due to cardiovascular diseases in children especially when high doses of GH were used [11] .…”
mentioning
confidence: 99%